حماية الملكية الفكرية في التشريع االجزائري واالتفاقيات الدولية - لعالوي وصال ✓ أوذينةمنال (جامعة المسيلة, 2024)
Information and creativity are considered the fruits of human thought, which later turn into a stock of knowledge that the nation benefits from and derives from it everything it needs to function in life. Therefore, the belonging of these ideas to their original owners must be recognized, and this is through their representation of their innovative works and their acquisition of intellectual property rights, but recognition is not enough. Due to the importance of these intellectual developments, as they have influenced the cultural and civilizational level of peoples, and have even contributed to the development of the modern economic system, which has prompted the international community to call for treaties and agreements to protect intellectual property rights from all forms of abuse. We do not deny that interest in protecting intellectual production has been present since ancient times, but it was not clearly apparent. This protection emerged in a tangible way in the wake of the Industrial Revolution and the technological innovations and inventions that accompanied it, especially with the dominance of the Internet over these rights and its becoming in a digital environment. Hence, intellectual property rights, both literary and artistic, represented by copyright and related rights, as well as industrial rights, mainly represented by patents, received the attention of countries and were granted protection at the national and international levels. We find that the Algerian legislator has organized legislation on intellectual property issues and given it great importance by addressing most of the crimes affecting it and has approved penal protection and judicial and administrative measures for it by establishing special laws and regulations to protect it from all forms of abuse. This is in keeping